Engaging Those Living With Moderate to Severe TBI and Their Caregivers in Research. (3rd March 2021) - Mohatt, Nathaniel V; Kreisel, Carlee J; Brenner, Lisa A
Despite the fact that millions of individuals living in the United States are coping with disabilities associated with traumatic brain injury (TBI), limited work has explored strategies for patient engagement in research among those with such injuries. The Coalition for Recovery and Innovation in Traumatic Brain Injury Care Across the Lifespan (CRITICAL) brought together those living with TBI, caregivers, clinicians, researchers, and advocates with the goal of developing a new patient-centered research agenda. This platform was also used to explore strategies to engage those with moderate to severe TBI in the research process. The CRITICAL was formed of 6 survivors of moderate to severe TBI, 2 caregivers of survivors of moderate to severe TBI, and 8 TBI professionals. The CRITICAL identified 3 priority topic areas: Relationship Quality, Caregiver Needs, and Thriving. Furthermore, strategies associated with Communication, Preparation, and the Environment facilitated research engagement. Employing the strategies outlined in this article is expected to promote patient engagement in clinical research, which can improve patient-centered interventions and outcomes for individuals living with TBI.